Feasibility of self-administered dried blood spot collection for cardiometabolic profile analysis in a population-based sample of young adults - Katherine M. Livingstone; Kathleen M. Dullaghan; Jeffrey M. Craig; Barbara Brayner; Sarah A. McNaughton (PLoS ONE, 2025)
Young adults may have poor cardiometabolic health that is undetected due to infrequent health checks. Feasibility of self-administration of blood samples using dried blood spot (DBS) cards for remote screening of this population group is unknown. The primary aim of this study was to examine the feasibility of collecting self-administered blood samples using DBS cards for cardiometabolic profile analysis in a population-based sample of young adults. Between April and November 2022, Australian young adults (18–30 years) completed an online survey and were mailed a self-administered DBS collection kit. Participants completed an open-ended question on any difficulties with the blood collection process. Samples were returned for an 8-item cardiometabolic profile analysis. Of the 506 participants mailed a collection kit, 72% (n = 366; mean 23.5 [SD 3.9] years; 53% female) returned their samples. Of mailed collection kits, 46% (n = 235 of 506) of participants returned samples that were adequate for all eight cardiometabolic profile measures. The participants who reported difficulties with the process (63%; n = 313) were followed up twice, on average (range 1–12 times), by the researcher to provide support, of which n = 155 proceeded to provide an adequate sample for all eight cardiometabolic measures. A lack of blood (75%; n = 235) was the most reported difficulty with sample collection. With the provision of support, self-administered dried blood spot collection for cardiometabolic profile analysis shows promise in a population-based sample of young adults.